VD_FINDINFO Jug / 2025 / 133 vom 2. Juli 2024 - VD Tribunal cantonal (2024)
DIFFAMATION, REJET DE LA DEMANDE, ACQUITTEMENT, AVANCE DE FRAIS | 173 CP, 174 CP, 10 CPP (CH), 139 CPP (CH), 389 CPP (CH), 433 al. 2 CPP (CH)